The Study of Alternative Wooden House Construction base on People Ability - Poomchalit W; Suzuki K; Suzuki A (Bandar Lampung University (UBL), 2017)
For communities in Thailand that carries day-time dwellers of aging people, women and children especially old communities that is mostly contained of wooden houses, strength of building structure has been depended upon the ability of maintenance of people. Even wooden houses are generally seen but craftsman carpenters are not enough available and more expensive. Thought, they are easily built with basic tools and skill as cutting and hammering but, their strength is varied because they are also related to personal vitality and ability in construction and budget. Under the study framework, the relationship of personal construction ability and load carrying of structure are the main consideration to explore an appropriated method of wooden house reconstruction that is strongly enough for live load, easy for everyone to build and reduce the cost. It must promote sustainable conservation and development while it is contributing sufficiency living. So, actual load carrying has been investigated by measuring of house and furniture before calculating. An ability has been tested by target groups’ workshops. The data has been classified by types of material; reused woods and general construction woods, basic tools as hammer and nails and 2 methods of construction; cutting and joining. Two data has been compared and matched together to find the decent alternative. It seems that, the alternative material probably suitable for people’s ability but it needs more design to strengthen and makes it easy to construct